Ungulates and trains – Factors influencing flight responses and detectability. (1st July 2022) - Bhardwaj, Manisha; Olsson, Mattias; Håkansson, Emma; Söderström, Pär; Seiler, Andreas
Abstract: Wildlife-train collisions can have deleterious effects on local wildlife populations and come with high socio-economic costs, such as damages, delays, and psychological distress. In this study, we explored two major components of wildlife-train collisions: the response of wildlife to oncoming trains and the detection of wildlife by drivers. Using dashboard cameras, we explored the flight response of roe deer ( Capreolus capreolus ) and moose ( Alces alces ) to oncoming trains and explored which factors, such as lighting and physical obstructions, affect their detection by drivers. In a majority of cases, roe deer and moose fled from an oncoming train, at an average flight initiation distance (FID) of 78 m and 79 m respectively. Warning horns had unexpected influences on flight behaviour. While roe deer initiated flight, on average, 44 m further away from the train when warned, they usually fled towards the tracks, in the direction of danger. FID of moose, however, was unaffected by the use of a warning horn. As train speed increased, moose had a lower FID, but roe deer FID did not change. Finally, detection of wildlife was obstructed by the presence of vegetation and uneven terrain in the rail-side verge, which could increase the risk of collisions. Our results indicate the need for early detection and warning of wildlife to reduce the risk of collisions. We propose that detection systems should include thermal cameras to allow detection behind vegetation and in the dark, and warning systems should use cues early to warn of oncoming trains and allow wildlife to escape the railway corridor safely. Highlights: Dashboard cameras can be used to evaluate ungulate reactions to oncoming trains. Roe deer and moose tend to flee from trains, but often onto or across the tracks. Detection of wildlife was obstructed by rail-side vegetation and terrain. To reduce risk of collisions, we suggest the use of thermal cameras and early acoustic warning.